The Port of Trieste (Northern Adriatic Sea)—A Case Study of the “Ecosystem Approach to Management” - Cibic, Tamara; Franzo, Annalisa; Nasi, Federica; Auriemma, Rocco; Del Negro, Paola (Frontiers in Marine Science, 2017)
This study is a rare example of “the ecosystem approach to management” that has been carried out for the purpose of providing practical support to decision-makers in managing a Site of National Interest (SIN) where activities such as fishing, aquaculture and swimming are restricted. Benthic ecosystem functioning was assessed to verify whether it would be possible to exclude the less contaminated part from the SIN and its legislative constraints. At five macrosites subjected to diversified industrialization and anthropization, we evaluated the structural characteristics of the sediments, both heterotrophic and phototrophic communities, and the main processes of production, transformation and consumption of organic matter at seven stations, plus a reference site. Along the north-eastern boundary of the bay, the port, shipbuilding and iron foundry areas, characterised by high levels of contaminants, low macrozoobenthic diversity, major organic contents (up to 51.1 mgC g-1) and higher numbers of hydrocarbon degrading bacteria (up to 5,464 MPN gdry-1), differed significantly (RANOSIM = 0.463, p = 2.9%) from the other areas (stations). Oxygen consumption (-15.221.59 mgC m-2) prevailed over primary production and the trophic state was net heterotrophic. In contrast, on the other side of the harbour (residential area/centre bay), contamination levels were below the legal limits and both the microalgal and macrobenthic communities displayed higher biodiversity. Higher macrofaunal abundances (up to 753174.7 ind.m-2), primary production rates (up to 58.608.41 mgC m-2) and exoenzymatic activities were estimated. nMDS and SIMPROF analyses performed on benthic communities significantly separated the most contaminated stations from the other ones. Overall, by applying this holistic approach, a better environmental situation was highlighted along the southern boundary of the bay and according to these results this part of the bay could be excluded from the SIN. However, further sampling is required along a finer sampling grid in the less contaminated side of the port in order to confirm these first results. Our work is one of the first case studies where such an ecosystem approach has been applied to a port area, in order to provide practical support to decision-makers involved in the spatial planning of harbour zones.